Los feriados patrióticos en la memoria colectiva: lo que se recuerda y se olvida. (1979-2000) - Gólcher Barguil, Erika (2016)
In this research we aim to identify and analyze the collective memory of Costa Rica from school holidays in the texts of civic ephemera relating to the homelands. This will lead us to understand the concepts in the text of civic spaces become political socialization and we emphasize the important developments in Costa Rican history that are forgotten in the texts. These elements have a continuous socialization process in the country to produce active citizens in their political role and identified with their homeland. Despite some shortcomings and omissions holding patriotic holidays is revealed significant and important in the internalization of patriotic values. We conclude that the framework of Costa Rican citizens, the lens through which reality is configured looks from civic education and what is remembered and remains in the collective memory.